The Potential of Hybrid Learning Models in Improving Students' Critical Thinking Ability - Hernawan Sulistyanto (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Critical thinking is important in education because it encourages students to gain a more complex understanding of information. High critical thinking skills will lead students to find and conclude their own understanding, and will facilitate convenience in the world of work. This study aims to test a hybrid learning model concept in empowering students' critical thinking skills. Hybrid learning extracts advantages from elements of learning styles, online learning, and open-ended learning. The research method uses quantitative research procedures. The test results show that the hybrid learning model has the potential to significantly empower students' critical thinking skills compared to the conventional model.